Pest survey card on Bactrocera zonata. Issue 1 (29th January 2021) - ,; Mertens, Jan; Schenk, Martijn; Delbianco, Alice; Graziosi, Ignazio; Vos, Sybren
Abstract : This pest survey card was prepared in the context of the EFSA mandate on plant pest surveillance (M‐2020‐0114), at the request of the European Commission. Its purpose is to guide the Member States in preparing data and information for Bactrocerazonata surveys. These are required to design statistically sound and risk‐based pest surveys, in line with current international standards. Bactrocerazonata is a clearly defined taxonomic entity.Imports of fruits of Prunus speciesand several other hosts are currently subject to specific measures aiming to prevent entry ofnon‐European Tephritidae.Nevertheless, the most likely introduction of B. zonata would be via transport of infested fruit followed by gradual natural spread. Bactrocerazonata is currently absent from the EU and surveys would therefore be aimed at substantiating pest freedom. Adult trapping is the preferred survey method for the detection of B. zonata . The preferred timing for surveillance is during the summer months when abundant fruits are available from the main host plants. Bactrocerazonata is a polyphagous species that has currently been reported to attack over 50 cultivated and wild plant species. The primary host for detection surveys in the EU would be cultivated peaches and nectarines, whereas other host species should be includedin case of delimiting surveys. Bactrocerazonata is expected to be able to establish in the southern part of the EU. Identification of B. zonata at the species level requires morphological examination of adults and molecular protocols are available.